1.5-MHz repetition rate passively Q-switched Nd:YVO4 laser based on WS2 saturable absorber *Project supported by the National Natural Science Foundation of China (Grant No. 61378024). (April 2017) - Wang 王, Xi 茜; Li 李, Lu 璐; Li 李, Jin-Ping 金萍; Wang 王, Yong-Gang 勇刚
Abstract : A transmission-type tungsten disulfide (WS 2 ) -based saturable absorber (SA) is fabricated and applied to passively Q-switched Nd:YVO4 laser. The WS2 nanosheets are deposited on a quartz substrate by the vertical evaporation method. By inserting the WS2 SA into the plano-concave laser cavity, we achieve 153-ns pulses with an average output power of 1.19 W at 1064 nm. To the best of our knowledge, both of them are the best results among those obtained by the Q-switched solid-state lasers with WS2 -based absorbers. The repetition rate ranges from 1.176 MHz to 1.578 MHz. As far as we know, it is the first time that MHz level Q-switched pulses have been generated in all solid state lasers based on low-dimensional materials so far.